Visual integration of direction and orientation information in autistic children. (February 2017) - Manning, Catherine; Tibber, Marc S; Dakin, Steven C
Background and aims: The vision of autistic people has been characterised as focused on detail, with a disinclination (or reduced ability) to integrate information into coherent 'wholes'. In contrast to this view, we recently demonstrated enhanced integration of visual motion signals in autistic children compared to typically developing children. Here, we aimed to investigate the robustness of our finding of increased motion integration in autism with a new sample of children and to determine whether increased integration in autistic children would extend to a static, orientation judgement. Methods: We presented motion and orientation equivalent noise and coherence tasks to 46 autistic children aged 6 to 14 years and 45 typically developing children matched in age and non-verbal IQ. The equivalent noise tasks consisted of two interleaved conditions: a high-noise condition in which children judged the average direction or orientation of elements whose range of direction or orientations was manipulated, and a no-noise condition in which children judged the direction or orientation of elements sharing the same direction or orientation. Equivalent noise modelling provided estimates of internal noise (the precision with which children can estimate the orientation/direction of one element) and global sampling (how many elements children are effectively using to judge the overall orientation/direction). Children also completed coherence tasks in which the proportion of signal elements sharing the same direction or orientation amidst otherwise random noise elements was manipulated. We assessed group differences using a combination of frequentist and Bayesian statistical approaches. Results: Analysis of the data in this new sample alone did not provide sufficient evidence either in favour or against the hypothesis of increased integration in autism. However, when combining motion data from this and the original experiment, autistic children exhibited superior integration of direction information in the high-noise condition compared to typically developing children, with similar no-noise and coherence thresholds. Equivalent noise modelling of these data revealed increased sampling in autistic children for motion information but no conclusive evidence for atypical levels of internal noise. There was no evidence of differences between autistic and typically developing children in the orientation equivalent noise and coherence tasks. Conclusions: Overall, autistic children effectively integrated more direction information than typically developing children. However, the groups overlapped considerably and there was substantial individual variability, so that the effect may be difficult to detect in small groups. There was no indication of atypical integration of orientation in the current study, although larger samples will be required in order to provide conclusive evidence. Implications: These results help characterise the nature of sensory processing in autism, which is of high import and relevance given the recent inclusion of sensory symptoms in diagnostic criteria. Increased integration of motion information could potentially lead to feelings of sensory overload in autistic children. If such increased integration is specific to motion information, domain-specific accounts of autistic perception will be required.